The Use of the RETeval Portable Electroretinography Device for Low-Cost Screening: A Mini-Review - Saad, Amr; Turgut, Ferhat; Sommer, Chiara; Becker, Matthias; DeBuc, Delia; Barboni, Mirella; Somfai, Gabor Mark (Klinische Monatsblätter für Augenheilkunde, 2024)
Electroretinography (ERG) provides crucial insights into retinal function and the integrity of the visual pathways. However, ERG assessments classically require a complicated technical background with costly equipment. In addition, the placement of corneal or conjunctival electrodes is not always tolerated by the patients, which restricts the measurement for pediatric evaluations. In this short review, we give an overview of the use of the RETeval portable ERG device (LKC Technologies, Inc., Gaithersburg, MD, USA), a modern portable ERG device that can facilitate screening for diseases involving the retina and the optic nerve. We also review its potential to provide ocular biomarkers in systemic pathologies, such as Alzheimerʼs disease and central nervous system alterations, within the framework of oculomics.
Keywords: electrophysiology; glaucoma; neuroophthalmology; pediatric ophthalmology; retina